Introduction to architecting for the Cloud--Amazon AWS : fundamental strategies and best practices - Hand, Daniel; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2015)
"In this Introduction to Architecting for the Cloud - Amazon AWS training course, expert author Daniel Hand will teach you the strategies and best practices used to efficiently and securely incorporate the AWS cloud into technology platforms. This course is designed for the absolute beginner, meaning no previous Amazon AWS experience is required. You will start by learning about design principles and patterns, including cloud concepts, VPC design patterns, and integration strategies. From there, Daniel will teach you about availability, cost optimization, performance, and scalability and durability. This video tutorial also covers security, including network access controls, security groups, encryption, and logging. Finally, you will learn about Amazon deployment and management services. Once you have completed this computer based training course, you will be fully capable of incorporating the AWS cloud into your organization's technology platform."--Resource description page.
Title from title screen (viewed July 22, 2015)
Date and publisher taken from resource description page.
Presenter, Daniel Hand.
Keywords: Amazon.com (Firm); Web services; Cloud computing; Electronic books